PARASITOLOGICAL MONITORING OF FISH FARM FACTORIES - A. M. Naumova; A. Yu. Naumova (Российский паразитологический журнал, 2016)
Objective of research: to perform the parasitological monitoring we have to study the parasite fauna in fishes from different fish farm factories, calculate the index of similarity, estimate the influence of abiotic and biotic factors on the ecosystem of fish-breeding reservoirs. Materials and methods: parasitological monitoring of factory fish farms was conducted by the method of complete and incomplete parasitological examination taking into account the data obtained from various fish-breeding reservoirs. Results and discussion: the parasite fauna of cyprinid fishes is represented by 56 species, carriage of causative agents of parasitic diseases in fishes is detected. Index of similarity of parasite fauna in carps has been studied and typification of agricultural reservoirs carried out. Index of  similarity between the parasite fauna in carp and herbivorous fish was 22–33 %, carp and rough fish - 18–30,7 %. Influence of abiotic (oxidability, reduction of oxygen and nitrogen ammonia concentration, mineralization) and biotic – anthropogenic factors (violation of processing technologies, veterinary and sanitary rules of fish transport and fish farming operations) on fish infestation with parasites was studied. The role of parasitological monitoring in prevention and elimination of fish diseases was shown.